Jenis-Jenis Pakan Alami Leptobarbus melanopterus di Taman Nasional Danau Sentarum Kabupaten Kapuas Hulu - Ari Hepi Yanti, Cristiar Samosir, Tri Rima Setyawati, (Jurnal Protobiont, 2019)
As the endemic fish of Danau Sentarum National Park, peam fish or Leptobarbus melanopterus had environmental problem such as overfishing due which threaten either juvenile or adult fish. These conditions were feared will led L. melanopterus population decrease in future if there is no sustainable management such as aquaculture. This research aims to identify the natural foods of L. melanopterus. Sixty four samples of L. melanopterus were collected through purposive sampling method. The results of gut analysis were found 17 genera of phytoplankton, 4 genera of zooplankton, 1 plant, and 1 Insecta. Zygnematophyceae had the most various genera which consisted of 7 genera while Ulvophyceae and Xanthophyceae only had 1 genera each of them. The natural food of L. melanopterus can be used as preliminary data for the application of aquaculture in the future.